PENERAPAN GOAL SETTING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA : PENDEKATAN EKSPERIMEN NON RANDOMIZED CONTROL TRIAL - Dian Anggun Angraeni; Effy Wardati Maryam; Ghozali Rusyid Affandi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Confidence is the main key for students to be able to find themselves when they are in the school environment and in a social environment, with self-confidence students are also able to develop their talents, interests and potential. Students who have low self-confidence will cause problems in themselves. One of the factors to increase student self-confidence is by being given goal setting training. This study aims to determine the effect of goal setting training to increase self-confidence in students. In this study students will be given treatment in the form of goal setting training given to the experimental group. The subjects to be studied were students of Yapalis Krian Vocational School, totaling 41 students for the experimental group and 41 students for the control group. The measuring tool used to measure the level of self-confidence is the self-confidence adaptation scale (Pertiwi & Ansyah, 2021). The research design used a Non-Randomized Control Trial Experiment, because the determination of subjects was not done randomly. Independent Sample T-test parametric statistical analysis was used to determine differences in group and control group self-confidence scores, while to see differences in pre-test and post-test scores using the Paired Sample T-test. The results showed that there were differences in the level of self-confidence of students in the experimental group and the control group before and after goal setting training